The ventilation of multiple-bed hospital wards in the tropics: A review - Yau, Yat Huang; Chandrasegaran, D.; Badarudin, Ahmad (Elsevier, 2011)
Hospital and healthcare facilities have diverse indoor environment due to the different comfort and health needs of its occupants. Currently, most ventilation studies revolve around specialised areas such as operating rooms and isolation rooms. This paper focuses on the ventilation of multiple-bed hospital wards in the tropical climate, taking into account the design, indoor conditions and engineering controls. General ward layouts are described briefly. The required indoor conditions such as temperature, humidity, air movements and indoor air quality in the ward spaces are summarized based on the current guidelines and practices. Also, recent studies and engineering practices in the hospital indoor environment are elaborated. Usage of computational fluid dynamics tools for the ventilation studies is discussed as well. As identified during the review, there is an apparent knowledge gap for ventilation studies in the tropics compared with temperate climates, as fact studies have only been published for hospital wards in countries with a temperate climate. Therefore, it is highlighted that specific tropical studies along with novel engineering controls are required in addressing the ventilation requirements for the tropics. © 2010 Elsevier Ltd.